Helminth Parasites of Clarias gariepinus (Clariidae) in Lekki Lagoon, Lagos, Nigeria - B., Akinsanya (Universidad de Costa Rica, 2006)
A total of 360 randomly selected specimens of Clarias gariepinus (Clariidae) recovered from Lekki Lagoon were examined for intestinal helminth parasites. Parasite prevalence and worm burden were low; 17 (4.72%) of the specimens examined were infected with gastrointestinal helminths. The helminth worms recovered include, three cestodes Polyonchobothrium clarias, Stocksia pujehuni and Wenyonia acuminata and a nematode, Paracamallanus cyathopharynx. There was no statistically significant difference in the infection of the male and female Clarias gariepinus; the infection rates in male and female samples were 5.75% and 3.76% respectively. Parasite prevalence was related to the length and weight of the specimens.The fish samples were observed to show negative allometric growth and smaller samples recorded higher helminth infection.